Proposal for an Alternate Structure to Organize and Access Resources in a Virtual Library in Education - Hudon, Michèle (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Description of the stages of development of a faceted classification structure usable to organize and access a virtual collection of specialized web resources in the field of education. Comments on the results of a first application of the newly established structure. Présentation des étapes de développement d’une structure classificatoire à facettes utilisable pour l’organisation et l’accès à une collection virtuelle de ressources du web spécialisées dans le domaine de l’éducation. Commentaires sur les résultats d’une première utilisation de la structure à facettes nouvellement établie.